PENGARUH DEBT TO ASSETS RATIO DAN CURRENT RATIO TERHADAP RETURN ON ASSETS PERUSAHAAN KOSMETIK & BARANG KEPERLUAN RUMAH TANGGA YANG TERCATAT DI BURSA EFEK INDONESIA - Chrestella Archel Indiarsusilo; Zulkifli Zulkifli (Gapenas Publisher, 2023)
This study aims to test and analyze the effect of debt to assets ratio and current ratio on return on assets. This research approach is with quantitative research. The research population is cosmetic and household appliance companies listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling with the determination of criteria, namely cosmetic companies and household appliances that are consistently recorded according to the observation period for analysis in the study. Types of research data with secondary data whose collection method uses audited financial statement data. Data analysis method with panel data regression analysis. These empirical findings determine the best model, namely fixed effect and it is proven that the debt to asset ratio has a negative and significant effect on return on assets. Meanwhile, the current ratio does not have a significant effect on the return on assets